Development of Arc Welding Teaching Aid for Padding Training - Asman, Nur Ariff; Wan Muda, Wan Hanim Nadrah (Research and Innovation in Technical and Vocational Education and Training, 2021)
This study is to develop Training Aid Arc Welding For Padding Training. The design of the study is product development and identification of product suitability as training aid. The Hanaffin & Peck model is used as a guide in developing products as training aid. The data obtained were analyzed using frequency and percentage descriptive data to see if the training aid produced could be used for the practical learning. The findings show the high value of training aid usage. Expert confirmation was 3 people consisting of a lecturer and a technician from FPTV, UTHM while a lecturer from the ILP Pasir Gudang. It can be concluded that design of Training Aid Arc Welding For Padding Training is suitable as a tool used in practical learning and specifically in pading training to help students learn to control three welding processes namely arc distance, electrode angle and electrode movement speed for the subject of metal fabrication skills at UTHM.